Magnetic resonance imaging for preoperative diagnosis in third molar surgery: a systematic review - Al-Haj Husain, Adib; Stadlinger, Bernd; Winklhofer, Sebastian; Piccirelli, Marco; Valdec, Silvio (Oral radiology, 2023)
In recent years, magnetic resonance imaging (MRI) has made great strides through various technical improvements and new sequences, which have made it one of the most promising and leading imaging techniques in the head and neck region. As modern imaging techniques in dentistry aim to reduce radiation exposure, this systematic review evaluated the possibilities, advantages, and disadvantages of advanced imaging diagnostics using dental MRI and its evidence for clinical indications and limitations relevant to mandibular third molar (MTM) surgery. Two reviewers performed multiple database searches (PubMed MEDLINE, EMBASE, Biosis, and Cochrane databases) following the PICOS search strategy using medical subject headings (MeSH) terms, keywords, and their combinations. Ten studies were included in this systematic review. By providing high spatial resolution and excellent soft tissue contrast, black bone MRI sequences such as 3D Double Echo Steady State (DESS) and 3D Short Tau Inversion Recovery (STIR) imaging protocols have the potential to become a valuable alternative to cone-beam computed tomography (CBCT) in future dental clinical routines. Overall, radiation-free MRI represents another step toward personalized dentistry and improved decision-making that avoids ineffectiveness and minimizes risks in oral surgery by taking into account additional patient-side factors such as comorbidity, anatomical norm variations, and imaging biomarkers.